MANAJEMEN SUMBER DAYA PENDIDIKAN ISLAM - Andita Dwi Puspita Ningsih; Sri Minarti (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Islamic education resource management is an important aspect in achieving the goal of quality education, which not only focuses on increasing knowledge, but also on the formation of a generation of faith, knowledge and morals. The purpose of this study is to describe the challenges faced and managerial strategies that can be applied in managing Islamic education resources. This research uses a descriptive qualitative approach, with data collection through literature studies, interviews, and observations of management practices in Islamic educational institutions. The results show that Islamic education resource management faces various challenges, such as limited resources, lack of infrastructure, and the quality of human resources that still need to be improved. To overcome these challenges, this study proposes several strategies, including strategic planning, human resource development, material and financial resource management, and continuous monitoring and evaluation. In its implementation, the role of the government and Islamic education institutions is very important to improve the quality of management and provide adequate facilities. With the implementation of appropriate strategies, efficient management of Islamic education resources can help achieve optimal Islamic education goals.